2020
DOI: 10.3389/fphar.2020.594591
|View full text |Cite
|
Sign up to set email alerts
|

“Tobacco Is the Chief Medicinal Plant in My Work”: Therapeutic Uses of Tobacco in Peruvian Amazonian Medicine Exemplified by the Work of a Maestro Tabaquero

Abstract: Introduction: Harmful usage of tobacco is a public health problem of global concern and, in many countries, the main risk factor for non-communicable diseases. Yet, in the Peruvian Amazon, the geographical region believed to be tobacco's historical birthplace, this plant is associated with a strikingly different usage and repute: Tobacco (especially Nicotiana rustica L.) in this area is described as a potent medicinal plant, used topically or via ingestion to treat a variety of health conditions. The goal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 109 publications
0
32
0
2
Order By: Relevance
“…Applied indiscriminately in the context of plant medicines such as ayahuasca, they may serve as a justification to dismiss the indigenous knowledge and practices around the usage of such plants as merely symbolic. However, drawing on our data and the corresponding literature presented, we suggest that experienced and trained curanderos who work with so-called "master plants" would not accept a purely symbolic interpretation of their methods-preferring instead to highlight aspects of their experience (subtle, energetic, spiritual) which they consider indispensable when using plants that induce altered states of consciousness (Andritzky, 1989;Mabit, 2007;Dobkin de Rios et al, 2008b;Berlowitz et al, 2017;Sharrock, 2018;Berlowitz et al, 2020), and pointing also to their exercise of effective techniques that can be learned using indigenous training methods (such as the diet). While it is in principle possible to reduce ayahuasca to what could be considered its "active components" (i.e., DMT and the β-carbolines)-standardizing the substance ("pharmahuasca") and manualizing the intervention (i.e., a double reduction of the plant material and associated dynamic rituals)-such an approach could possibly even reduce therapeutic potential, not to mention threatening to marginalize the very sources of those healing practices which have so captured the attention of the West in the first place.…”
Section: Concluding Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Applied indiscriminately in the context of plant medicines such as ayahuasca, they may serve as a justification to dismiss the indigenous knowledge and practices around the usage of such plants as merely symbolic. However, drawing on our data and the corresponding literature presented, we suggest that experienced and trained curanderos who work with so-called "master plants" would not accept a purely symbolic interpretation of their methods-preferring instead to highlight aspects of their experience (subtle, energetic, spiritual) which they consider indispensable when using plants that induce altered states of consciousness (Andritzky, 1989;Mabit, 2007;Dobkin de Rios et al, 2008b;Berlowitz et al, 2017;Sharrock, 2018;Berlowitz et al, 2020), and pointing also to their exercise of effective techniques that can be learned using indigenous training methods (such as the diet). While it is in principle possible to reduce ayahuasca to what could be considered its "active components" (i.e., DMT and the β-carbolines)-standardizing the substance ("pharmahuasca") and manualizing the intervention (i.e., a double reduction of the plant material and associated dynamic rituals)-such an approach could possibly even reduce therapeutic potential, not to mention threatening to marginalize the very sources of those healing practices which have so captured the attention of the West in the first place.…”
Section: Concluding Discussionmentioning
confidence: 84%
“…The use of plants is central in Amazonian medical traditions. As urban hospitals are often remote and not accessible for indigenous and mestizo communities, the medicinal use of plants can account for treatments across a very broad range of illnesses and health conditions, which points to a long-standing indigenous medicine ( Berlowitz et al, 2020 ; Jauregui et al, 2011 ; Sanz-Biset and Cañigueral, 2011 ). For example, an initial community survey of medicinal plants by Sanz-Biset et al (2008) in the Chazuta 1 region of Peru revealed 318 different plants with a wide variety of application: from physical problems like infections, stomach pain, lumbago, headaches, scabies, bronchitis, malaria, diarrhoea, toothache, snake bites, broken bones, and wound care, to general health tonics (e.g., for giving vitality), preparations for hunting (applicable to both humans and dogs), rites of passage for adolescents, augmented work performance and reduced laziness, sharpened senses, increased sexual vitality, the attainment of special abilities for shamans, and also the treatment of conditions believed to be caused by sorcery or evil spirits (e.g., mal de aire/gente ; Kamppinen, 1988 ; Sanz-Biset and Cañigueral, 2011 , Sanz-Biset and Cañigueral, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while ayahuasca is known to have an acceptable safety profile from a pharmacological perspective, 26 , 34 , 109 many of the Amazonian techniques used in Takiwasi are not yet well studied scientifically, despite indigenous and community usage of the same plants in medical and other contexts. 59 , 63 , 110 , 111 Thus although Takiwasi’s exclusion criteria, 56 , 65 biomedical evaluation, and practitioner expertise likely increase the safety margin—particularly for international and urban patients where interactions not seen in traditional settings increase in likelihood (e.g. pharmaceutical interactions)—further study is needed on the basic effects of Amazonian medicinal plants and practices.…”
Section: Discussionmentioning
confidence: 99%